CBC Complex Regulates Hyphal Growth, Sclerotial Quantity, and Pathogenicity in the Necrotrophic Fungus Botrytis cinerea - Yinshan Zhang; Xueting Chen; Guihua Li; Qingming Qin; Mingzhe Zhang; Jianchun Qin (Journal of Fungi)
The cap-binding protein complex (CBC), comprising Cbp20 and Cbp80, is crucial for gene expression, yet its role in the notorious crop pathogen Botrytis cinerea remains unclear. Immunoprecipitation coupled with LC-MS/MS demonstrated that BcCbp20 interacts with BcCbp80. Yeast two-hybrid, GST pull-down, and Split-luciferase complementation assays confirmed that the conserved RNA recognition motif (RRM, 54–127 aa) of BcCbp20 and the N-terminal MIF4G domain (1–370 aa, 1–577 aa) of BcCbp80 constitute the core interaction regions. Genetic transformation experiments revealed that BcCBP80 exerts a more dominant role than BcCBP20 in regulating hyphal morphology, growth rate, conidiophore development, and conidial yield. Furthermore, BcCBP20 and BcCBP80 differentially regulate sclerotium formation to maintain sclerotial quantity. Based on pathogenicity assays, BcCBP80 associated with infection cushion development, with this phenotypic alteration possibly being among the factors correlated with altered pathogenicity. However, the increased sensitivity of ΔBccbp20 to various stress factors may be the primary reason for the diminished pathogenicity. Taken together, these results indicate that BcCBP20 and BcCBP80 play important roles in multiple aspects of B. cinerea growth, development, stress response, and pathogenicity.